Evaluation of the Abaxis Piccolo Point-of-Care Chemistry Analyzer: Comparison to the Roche Cobas C501. Issue 2 (June 2017) - Lee-Lewandrowski, Elizabeth; Flood, James; Zak, Richard; Griggs, David; Lewandrowski, Kent
Abstract : Abstract: In this study, we performed method validations for the Abaxis Piccolo Xpress assays for total protein, albumin, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, total bilirubin, calcium, creatinine, urea nitrogen, and glucose compared with the Roche Cobas c501 analyzer. The validation included linear reportable range, imprecision, and assessment of accuracy and bias by method crossover. Although some biases between the methods were observed, these could be reconciled by adjustments to the normal reference ranges. Overall, we found that these assays performed at an accepted level for clinical use.